(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
10-Oxo-4,6,7,8,9,10-hexahydroprazolo[1,5-a][1]benzothieno[2,3-d]pyrimidine-3-carbaldehyde (2) was prepared by Vilsmeier-Haack reaction of 3-amino-2-methyl-5,6,7,8-tetrahydro[1]benzothieno[2,3-d]pyrimidin-4(3H)-one (1). Reaction of carbaldehyde derivative 2 with malononitrile afforded arylidene malononitrile 3. Cyclization of the latter compound with thiourea yielded pyrimidinethione 4. Interaction of carbaldehyde derivative 2 in presence of thiourea with keto- compounds such as ethyl acetoacetate, or acetylacetone, or dimedone or ethyl cyanoacetate gave pyrimidine derivatives 5-8. Hydrazinolysis of carbaldehyde derivative 2 gave the hydrazone 9. Reaction of the latter with phenyl isothiocyanate afforded thiosemicarbazone 10, which underwent cyclization with oxalyl chloride to give thioxoimidazolidinedione 11. Condensation of compound 2 with thiosemicarbazide furnished thiosemicarbazone derivative 12. Reaction of compound 2 with aminopyrazolone in the presence of an acid and/or a base afforded pyrazolones 13 and 14. Treatment of carbaldehyde derivative 2 with cyanoacetohydrazide gave acrylohydrazide 15. Interaction of the latter with carbon disulfide yielded mercaptooxadiazole 16.Â Condensation of compound 2 with acetylpyridazinone 17 produced chalcone 18. Reaction of Â compound 18 with malononitrile in pyridine gave cyanopyran 19, while its reaction with malononitrile in presence of ammonium acetate in ethanol yielded cyanopyridine 20. Structures of the newly synthesized products have been deduced on the basis of elemental analysis and spectral data. The synthesized compounds were screened for their antimicrobial activity.Â